REVISION OF THE GENUS HELIOPLASMôLITES (HELIOLITOIDEA) AND ITS FIRST RECORD FROM THE SILURIAN OF MONGOLIA - Bondarenko O.B. (My University, 2001)
The genus Helioplasmolites is revised and only three species are retained, including Hm. dzharensis sp. nov. from the Wenlockian of Northwest Mongolia; ten of the remaining species are transferred to the genera Diploepora, Helenolites, Hemiplasmopora, Lacerites, Mcleodea, Squameolites and? Bogimbailites, and nine are considered as incertae sedis.
Keywords: Silurian; Helioplasmolites; Mongolia; Paleozoic::Silurian; Палеозой::Силурийская